Tatapan Pria dan Objektifikasi Tubuh Perempuan: Potensi Kekerasan Berbasis Gender Online Pada Akun Instagram @ugmcantik - Hilmi, Ammar Mahir (Jurnal Wanita dan Keluarga, 2024)
The presence of Instagram as a photo and video sharing platform has enabled individual users to interact and exchange information easily anywhere and anytime. The various features owned by this platform also allow Instagram to become an instrument for users to achieve their goals and interests. However, in its development, accounts are often found that use the phrase 'beautiful' in choosing their account name. The use of the phrase 'beautiful' is then in line with the account's upload pattern which features various photos of women. This paper is intended to critically examine the potential for online gender-based violence on the @ugmcantik Instagram account, which features various uploads of women's photos. Using the concept of male gaze introduced by Laura Mulvey, this paper aims to explain how the process of objectification of women's bodies is displayed in the @ugmcantik Instagram account uploads that seem to be intended to fulfil the needs of male users' gazes. The methodology used in this paper is critical discourse analysis by examining the uploads of the @ugmcantik Instagram account which displays various photos, image captions, hashtags, and netizen comments related to the upload. The findings in this paper are that the @ugmcantik Instagram account in its upload pattern tends to make photos of women as objects of passive gaze and aesthetically packaged for the sake of increasing the reach and popularity of the account. The implications of using women's photos as objects can then be identified through comments that are sexist and demeaning to women.